A History of the Vote in Canada - Perrault, SteÃÂphane; Gibson Library Connections, Inc (Elections Canada, 2021)
'This publication presents a fascinating account of the struggles and reforms that have shaped Canada's electoral system from pre-Confederation times to the present day. Originally researched and published in 1997 and updated in 2007, this third edition -